Role of percutaneous cerclage wire in the management of subtrochanteric fractures treated with intramedullary nails - Vivek Trikha; Saubhik Das; Prabhat Agrawal; Arkesh M; Sunil Kumar Dhaka (Chinese Journal of Traumatology, 2018)
Purpose: Cerclage wire application has emerged as a potential therapeutic adjunct to intramedullary nailing for subtrochanteric fractures. But its popularity is plagued by the concern of possible negative effect on fracture zone biology. This study was intended to analyze the clinico-radiological outcome and complications associated with cerclage wire application. Methods: Retrospective analysis was performed on all the subtrochanteric fractures operated with intramedullary nailing between January 2012 and January 2016. After exclusion, 48 patients were available with an average follow-up of 20.8 months. Long oblique, spiral, spiral wedge or comminuted fracture configurations with butterfly fragments were particularly considered for cerclage wire application, which was employed by percutaneous cerclage passer in 21 patients. Assessment was done in terms of operation time, blood loss, quality of reduction, neck-shaft angle, follow-up redisplacement, union time, complications, and final functional evaluation by Merle d’Aubigne'-Postel score. Results: Average operation time and blood loss were significantly higher in cerclage group (p < 0.05). However, cerclage use substantially improved quality of reduction in terms of maximum cortical displacement (p = 0.003) and fracture angulation (p = 0.045); anatomical reduction was achieved in 95.23% of cases as compared to 74.07% without cerclage. Union time was shorter, although not statistically different (p = 0.208), in cerclage group. Four patients in non-cerclage group developed non-union, 2 of them had nail breakage. No infection or any other implant related complications were reported with cerclage use. Conclusion: Minimally-invasive cerclage wire application has proved to be beneficial for anatomical reconstruction in difficult subtrochanteric fractures, whenever applicable, without any harmful effect on fracture biology.